2015
DOI: 10.1038/nphoton.2014.321
|View full text |Cite
|
Sign up to set email alerts
|

Lasing in direct-bandgap GeSn alloy grown on Si

Abstract: Direct bandgap group IV materials may thus represent a pathway towards the monolithic integration of Si-photonic circuitry and CMOS technology.Although a group IV direct bandgap material has not been demonstrated yet, silicon photonics using CMOS-compatible processes has made great progress through the development of Si-based waveguides 12 , photodetectors 13 and modulators 14 . The thus emerging technology is rapidly expanding the landscape of photonics applications towards tele-and data communication as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
890
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,153 publications
(925 citation statements)
references
References 40 publications
27
890
1
7
Order By: Relevance
“…The achievable Sn concentration in this study is 6:2 at: %, fairly comparable with other techniques such as MBE and CVD that can achieve from 7 À 12 at: %. 15,42 The maximum Sn concentration we have achieved is also quite close to that required for a direct bandgap transition. 8 Future work building off this study will need to develop new fabrication steps to suppress the porosity for doses greater than 2:1 Â 10 16 ion cm À2 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The achievable Sn concentration in this study is 6:2 at: %, fairly comparable with other techniques such as MBE and CVD that can achieve from 7 À 12 at: %. 15,42 The maximum Sn concentration we have achieved is also quite close to that required for a direct bandgap transition. 8 Future work building off this study will need to develop new fabrication steps to suppress the porosity for doses greater than 2:1 Â 10 16 ion cm À2 .…”
Section: Discussionsupporting
confidence: 68%
“…[10][11][12][13][14] However, only recently has Wirths et al demonstrated a direct bandgap alloy conclusively, with strong photoluminescence and a lasing effect at a Sn content of %11 at: %. 15 The aforementioned properties, together with the possibility of full compatibility with current Si technology, make Ge 1Àx Sn x an attractive material. However, achieving high quality crystalline Ge 1Àx Sn x with above 6:5 at: %Sn is challenging as the material is unstable at high Sn concentration because the solid solubility of Sn in Ge at ambient temperature is about 0:5 at: % .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 To address the vision of a monolithically integrated light source module in a Si CMOS environment, intense research on the integration of III−V materials as well as that on band gap engineering of group IV semiconductors is applied to achieve direct band gap materials either in the form of strained Ge or SiGeSn alloy systems. 4,5 For these purposes, Germanium virtual substrates (VS) on large diameter Si wafers are considered as a central materials platform to enable these advanced technologies. Germaniumbased VS are usually obtained by exploiting the compositional grading of Si 1−x Ge x strain-relaxed buffer (SRB) layers to reduce the misfit dislocation density by gradually lowering the lattice mismatch of the heterostructure with respect to the final functional layer.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Nonetheless, in order to move toward real-market applications, several issues still have to be addressed such as the low laser operating temperature. In particular, an increase of the Sn content in the active material beyond ∼12 at.…”
mentioning
confidence: 99%